UNHEARD PSYCHE: EXPLORING VARIOUS FACETS OF WOMEN IN THE POETRY OF JAYANTA MAHAPATRA - Sharma, Aparna; Chowdhury, Mouli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Jayanta Mahapatra’s poetic world surrounds the vivid images of women as wives, whores, adolescent girls, rural women, and metropolitan women which echoes the plight of women to a great extent. Mahapatra has tragically explored the pains and tribulations of women, especially in a male-dominated society. Imbibing his obsessions towards loss, suffering, quest for self, grief, death, and sexuality, he introduces various facets of women in the chaotic world. The portrayal of women in the poetry of Jayanta Mahapatra explores an alienated world with an over-mounted confession. He expresses the harsh realities and struggles of women in establishing their own identity. His poetry deals with some prominent themes such as hunger, sexual assault, and starvation which lead women to live miserable lives. By depicting the world of women, Mahapatra’s reverence and hospitality towards women are quite mesmerizing and he considers them as an epitome of love and sacrifice.